Estudio retrospectivo de alteraciones radiográficas de la región lumbosacra en caninos y felinos, en la clínica veterinaria de la Universidad Antonio Nariño - Gómez Guáqueta, Pedro José (Universidad Antonio Nariño, 2023)
Lumbosacral instability is a common disease in small animals, mainly canines of medium to large breeds, affecting one or more nerve roots of the cauda equina, which are compressed by alterations in soft tissues and bones associated with the spine, generating instability in the lumbosacral segment. The objective of the present study was to determine the frequency of presentation of lumbosacral segment alterations, diagnosed with the help of digital radiographs in the veterinary clinic of the Antonio Nariño University